Exposure to AT1 Receptor Autoantibodies during Pregnancy Increases Susceptibility of the Maternal Heart to Postpartum Ischemia-Reperfusion Injury in Rats - Hui-Ping Wang (International Journal of Molecular Sciences, 2014)
Epidemiological studies have demonstrated that women with a history of preeclampsia have a two-fold increased risk of developing cardiovascular diseases in later life. It is not known whether or not this risk is associated with angiotensin II receptor type 1 autoantibody (AT1-AA), an agonist acting via activation of AT1 receptor (AT1R), which is believed to be involved in the pathogenesis of preeclampsia. The objective of the present study was to confirm the hypothesis that AT1-AA exposure during pregnancy may change the maternal cardiac structure and increase the susceptibility of the postpartum heart to ischemia/reperfusion injury (IRI). In the present study, we first established a preeclampsia rat model by intravenous injection of AT1-AA extracted from the plasma of rats immunized with AT1R, observed the susceptibility of the postpartum maternal heart to IRI at 16 weeks postpartum using the Langendorff preparation, and examined the cardiac structure using light and transmission electron microscopy. The modeled animals presented with symptoms very similar to the clinical symptoms of human preeclampsia during pregnancy, including hypertension and proteinuria. The left ventricular weight (LVW) and left ventricular mass index (LVMI) in AT1-AA treatment group were significantly increased as compared with those of the control group (p < 0.01), although there was no significant difference in final weight between the two groups. AT1-AA acting on AT1R not only induced myocardial cell hypertrophy, mitochondrial swelling, cristae disorganization and collagen accumulation in the interstitium but affected the left ventricular (LV) function and delayed recovery from IRI. In contrast, co-treatment with AT1-AA + losartan completely blocked AT1-AA-induced changes in cardiac structure and function. These data indicate that the presence of AT1-AA during pregnancy was strongly associated with the markers of LV geometry changes and remodeling, and increased the cardiac susceptibility to IRI in later life of postpartum maternal rats.